2018
DOI: 10.1101/358143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of mouse ultrasonic vocalizations using deep learning

Abstract: Abstract:Vocalizations are a widespread means of communication in the animal kingdom. Mice use a large repertoire of ultrasonic vocalizations (USVs) in different social contexts, for instance courtship, territorial dispute, dominance and mother-pup interaction. Previous studies have pointed to differences in the USVs in different context, sexes, strains and individuals, however, in many cases the outcomes of the analyses remained inconclusive.We here provide a more general approach to automatically classify US… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Furthermore, we note that almost all recordings of the same individuals are co-localized, indicating that within-subject differences in syllable repertoire are smaller than those between individuals. Although it has been previously shown that a deep convolutional neural network can be trained to classify USV syllables according to mouse identity with good accuracy [18], here we see that repertoire features learned in a wholly unsupervised fashion very nearly do the same, evidence that mice emit individually-stereotyped, stable vocal repertoires.…”
Section: Resultsmentioning
confidence: 49%
“…Furthermore, we note that almost all recordings of the same individuals are co-localized, indicating that within-subject differences in syllable repertoire are smaller than those between individuals. Although it has been previously shown that a deep convolutional neural network can be trained to classify USV syllables according to mouse identity with good accuracy [18], here we see that repertoire features learned in a wholly unsupervised fashion very nearly do the same, evidence that mice emit individually-stereotyped, stable vocal repertoires.…”
Section: Resultsmentioning
confidence: 49%
“…Mice produce USVs in diverse social contexts ranging from courtship to aggression (Neunuebel et al, 2015; Sangiamo et al, 2020; Warren et al, 2020). We tested DeepSS using audio from an intruder assay, in which an anesthetized female was put into the home cage and the vocalizations produced by a resident female or male were recorded (Ivanenko et al, 2018). The female USVs from this assay typically consist of pure tones with weak harmonics and smooth frequency modulations that are often interrupted by frequency steps (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SongExplorer provides the first interactive graphical interface to allow exploration, discovery, and segmentation of animal sounds using deep learning tools. While we have characterized SongExplorer and a particular instantiation of a neural network model using Drosophila courtship song, many kinds of animal sounds can be accurately classified using deep learning models (Chesmore and Ohya, 2004; Coffey et al, 2019; Ivanenko et al, 2018; Koumura and Okanoya, 2016; Parsons, 2001; Sattar et al, 2016; Steinfath et al, n.d.). The neural network classifier accuracy is only weakly dependent on sample size and the classifier attained greater than 90% accuracy at detecting D. melanogaster pulse song with just 100 labelled events.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative study of these “sounds” is facilitated by automated segmentation. However, heuristic segmentation algorithms sometimes have low accuracy and fail to generalize across species (Arthur et al, 2013; Chesmore and Ohya, 2004; Coffey et al, 2019; Ivanenko et al, 2018; Koumura and Okanoya, 2016; LaRue et al, 2015; Parsons, 2001; Sattar et al, 2016). Song segmentation is particularly challenging for low signal-to-noise sounds, such as those produced by many insect species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation